Effect Of Islamic Financial Literacy, Financial Management, And Mobile Banking On The Effectiveness Of Students’ Pocket Money Management - Gita Utami Arsyah; Samsul Bahcri; Muh. Yusuf Qamaruddin (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the influence of Islamic financial literacy, financial management, and mobile banking on the effectiveness of student pocket money management, driven by the low national levels of Islamic financial literacy and inclusion. Methodology: This research uses a quantitative explanatory approach with a cross-sectional design. Data were collected via Likert-scale questionnaires from 75 Pharmacy students at Universitas Muhammadiyah Palopo, selected through stratified random sampling, and analyzed using multiple linear regression in SPSS. Results: The results show that Islamic financial literacy (t = 2.446; p = 0.017), financial management (t = 3.309; p = 0.001), and mobile banking (t = 2.563; p = 0.013) each have a positive and significant effect. Novelty: This study presents an integrated analysis of Sharia principles and financial technology (mobile banking) within the specific context of health-science students. Findings: Financial management is identified as the most dominant factor (β = 0.367) affecting the effectiveness of pocket money management, with a total simultaneous contribution of 54.9%. Originality: The originality lies in the empirical evidence derived from the integration of religious literacy and digital banking behavior among students in a regional university setting. Conclusions: Enhancing Sharia financial literacy and digital banking accessibility can effectively optimize student financial behavior. Type of Paper: Research Article.